MENJAWAB PERMASALAH PUTUSNYA IKATAN PERKAWINAN DALAM ISLAM TELAAH KAJIAN YURIDIS NORMATIF - Asman Asman (Al-Maslahah : Jurnal Ilmu Syariah, 2022)
Marriage in Islam is the sunnatullah of the Prophet Muhammad, where the rights and obligations of husband and wife are reflected in the daily life between husband and wife. In Law Number 1 of 1974 concerning marriage is to form a happy and eternal family, each husband and wife help each other and complete in order to achieve physical and spiritual well-being. Happiness in the household often does not run smoothly so it is difficult to maintain the integrity of the household. Finally the husband and wife broke the marriage bond by divorce so that it ended up in the Religious Court. The purpose of this study was to determine divorce and the legal consequences of dissolution of marriage. This study uses the type of research in the form of a library or research library. In general, the research method used is normative juridical research, namely research whose data is directed and focused on research in the form of library materials. The results of this study are divorce factors are economic factors, lack of family harmony, domestic violence, low understanding of religious values, not understanding marriage law or the Marriage Law, lack of socialization by related parties who handle marriage and lack of responsibility in household. Divorce can eliminate the marriage bond so that after losing the marriage bond the wife is no longer lawful for her husband.